IMPLEMENTASI KEBIJAKAN PEMUNGUTAN RETRIBUSI NON TUNAI DI PINTU MASUK UTAMA PANTAI PANGANDARAN - Elnia Nur Aziza; Asep Nurwanda; Agus Nurulsyam Suparman (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the less than optimal Implementation of the Non-Cash Retribution Collection Policy at the Main Entrance of Pangandaran Beach. The purpose of this study is to determine the Implementation of the Non-Cash Retribution Collection Policy at the Main Entrance of Pangandaran Beach. The research method used is descriptive research using a qualitative approach. Primary data in this study were obtained from 5 (five) informants. Data collection techniques used are literature studies, direct data collection through observation, interviews, and documentation. Data analysis in this study was carried out by means of data reduction, data presentation, and drawing conclusions. The results of this study are that the Implementation of the Non-Cash Retribution Collection Policy at the Main Entrance of Pangandaran Beach shows that it has been running, specifically at the main entrance of Pangandaran Beach, entrance ticket payments only use non-cash payment methods, but what occurs in the field is still some visitors who use cash transactions. Therefore, the lack of commitment in non-cash transactions at the main entrance of Pangandaran Beach. So for the suggestions put forward, it is better for policy implementers to be expected to continue to be committed to implementing non-cash transactions at the main entrance of Pangandaran Beach. Then, visitors should be prepared to use non-cash payment methods at the main entrance to Pangandaran Beach.